Hegemoni Dibalik Hubungan Bilateral Tiongkok-Indonesia - Rissa Amanda (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2021)
China is the largest superpower country in Asia nowadays. With its popularity in the fields of technology, transportation, infrastructure and others has attracted ASEAN countries, including Indonesia, to become more interested in tightening cooperation with China. However, what is almost forgotten is how China takes advantage of this moment to expand its expansion to other countries and it starts from the nearest countries. In this study, the authors used qualitative research methods - descriptive analytic with Library Research data collection techniques. The purpose of this study is to see how hegemony in bilateral relations between Indonesia and China. The results are hegemonic practices exist in bilateral relations between Indonesia and China through the OBOR project and Mandarin Language Center institutions such as Confucius Institute.